Pengaruh Komunikasi Pemasaran Terpadu Terhadap Minat Beli Konsumen Pond’s Yang Dimediasi Oleh Brand Equity (Studi Kasus: Konsumen Produk Pond’s di Central Park Mall, Jakarta) - Viliaus, Caroline; Tobing, Rudolf L (Manajemen Bisnis Kompetensi, 2017)
The purpose of this study is to analyze the impact of brand equity mediation on the influence of integrated marketing communications to customers’ buying of Pond’s products. This study is based on customer behavior theory of buying interest depends on integrated marketing communications which mediated by brand equity. Data collection technique using interviews with questionnaires distributed to 105 respondents using PT Unilever Indonesia’s Pond’s products. Based on the results of path analysis revealed that brand equity positively significant mediated the effect of integrated marketing communications. In other words, it can be concluded that the positive effect of integrated marketing communication on buying interest will increase while brand equity increases. The study recommended that to increase customer buying interest, the companies should synchronize integrated marketing communications with brand equity.Keywords : integrated marketing communication, brand equity, buying interest, path analyzis, synchronize.